2020
DOI: 10.1002/jctb.6630
|View full text |Cite
|
Sign up to set email alerts
|

Microwave‐assisted pyrolysis of organometallic gel prepared through ternary combination of surfactants for fabrication of nano‐porous gamma alumina: adsorptive properties, characterization

Abstract: BACKGROUND In present work, γ‐Al2O3 nanoparticles, with uniform morphology and controllable size, were successfully fabricated by the microwave‐assisted pyrolysis of organometallic gels prepared through the application of aluminum nitrite, urea, glycine, and triple mixed surfactants. A series of pyrolysis reactions were carried out by the conventional and microwave treatments to achieve nano‐porous powders. The effects of different process factors, such as fuel composition, pyrolysis method, calcination temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Some recent studies reported the synthesis of CuONPs and Al 2 O 3 NPs by various techniques, including pyrolysis, sol-gel, sputtering, laser ablation and electrochemical reduction [23][24][25][26][27][28][29][30][31][32]. Sodeifian and Behnood [33] reported a microwave-assisted method for the synthesis of CuO/Al 2 O 3 nanocomposite for photocatalytic degradation of methylene blue removal from aqueous solution under UV irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…Some recent studies reported the synthesis of CuONPs and Al 2 O 3 NPs by various techniques, including pyrolysis, sol-gel, sputtering, laser ablation and electrochemical reduction [23][24][25][26][27][28][29][30][31][32]. Sodeifian and Behnood [33] reported a microwave-assisted method for the synthesis of CuO/Al 2 O 3 nanocomposite for photocatalytic degradation of methylene blue removal from aqueous solution under UV irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Salem et al. [ 204 ] obtained γ‐Al 2 O 3 using microwave‐assisted pyrolysis of an organometallic gel. The gel consisting of aluminum nitrate [Al(NO 3 ) 3 ·9H 2 O] and fuel (urea and glycine) was heated in the microwave oven with a frequency of 2.45 GHz and then calcined at 800 °C to produce gamma phase.…”
Section: Microwave Synthesis Of Nanoporous Materials and Their Applicationsmentioning
confidence: 99%
“…Porous metal oxides obtained via microwave‐assisted methods with their SSA values and potential applications are summarized in Table 6 . [ 175–215 ]…”
Section: Microwave Synthesis Of Nanoporous Materials and Their Applicationsmentioning
confidence: 99%
“…Here, inorganic salts acted as microwave absorber. The technique has also been expanded to fabricate nanoporous aluminum oxide and titanium dioxide (TiO 2 ) [ 117 , 118 ]. The exposure of microwave irradiation to the precursor solution prepared by mixing of titanium tetraisopropoxide with HCl or HBr resulted in the fabrication of nanoporous TiO 2 with an average pore size of 14.5 nm [ 118 ].…”
Section: Microwave-based Fabrication Of Nanoporous Materialsmentioning
confidence: 99%